Investigating and Studying the Modifications of Nano and Micro-sized Amorphous Materials Under the Influence of a High Energy Radiation - Sabri, Mohammed M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
This research explored the behavior of glass when bombarded by high-energy radiation, especially electron beams inside transmission electron microscopy (TEM). Six types of glasses are investigated under e-beam. The work is conducted using three types of TEMs of energies of 120, 200, and 300 keV. The findings show that these microscopies have a significant impact on the glass, as various observations were documented. Using a wide electron beam, morphology changes combined with bubble formation are observed in the glass. These changes are rounding and smoothening of glass edges and surfaces. In addition, the findings show that there is no material loss due to irradiation as confirmed by the energy dispersive X-ray spectroscopy. The results also show that high silica glass is very sensitive, while high boron glass is found to be less sensitive to irradiation. Using a smaller size electron beam, on the other hand, resulted in the fabrication of a nanoring/nanocrater in glass. The possible applications of this research can be in the protection and packaging of three-dimensional electronic equipment and nanoscale pattern formation through roughening of the external glass contour through phase separation and the opposite through local changing of a part of the glass through the pseudo-melting and the stability of loaded and un-loaded glasses to the irradiation. Furthermore, by generating a nanoring or a nanocrater through e-beam, the lithography process is successfully performed, as the effect of the electron beam is solely at the irradiation region, while the regions outside the e-beam remain unaffected